2003
DOI: 10.1097/00063198-200307000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic hydrothorax

Abstract: A hepatic hydrothorax is a pleural effusion that develops in a patient with cirrhosis and portal hypertension in the absence of cardiopulmonary disease. The pleural effusion is derived from ascitic fluid that enters the chest because of the negative pressure within the pleural space via defects in the diaphragm. The peritoneal-to-pleural flow of fluid can be demonstrated by nuclear scanning, even when the ascites is not clinically apparent. The pleural fluid usually has the characteristics of a transudate. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 48 publications
1
33
0
4
Order By: Relevance
“…It has been suggested that the most likely cause of hepatic hydrothorax is the direct passage of ascitic fluid from the peritoneal cavity to the pleural cavity through anatomical diaphragmatic defects [4,5]. Interestingly, tense peritoneal ascites is not constant in patients with hepatic hydrothorax [5][6][7]. Hepatic hydrothorax develops as a consequence of increased sodium retention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the most likely cause of hepatic hydrothorax is the direct passage of ascitic fluid from the peritoneal cavity to the pleural cavity through anatomical diaphragmatic defects [4,5]. Interestingly, tense peritoneal ascites is not constant in patients with hepatic hydrothorax [5][6][7]. Hepatic hydrothorax develops as a consequence of increased sodium retention.…”
Section: Introductionmentioning
confidence: 99%
“…The major risk of this procedure is pneumothorax, especially with serial thoracentheses [6]. Transjugular intrahepatic portosystemic shunt (TIPS) is the procedure of choice in patients with hepatic hydrothorax who do not respond to diuretic and thoracentheses [7,11]. However, serious complications are related to TIPS placement.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic hydrothorax is a rare but important cause of—usually unilateral—pleural effusion. About 85–90% of the cases are isolated right-sided effusions [6]. Hepatic hydrothorax can be observed as a complication of portal hypertension in <10% of patients with ascites secondary to advanced liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of HH is difficult and sodiumfluid restriction and diuretics are often not sufficient [2]. TIPS and liver transplantation may be a good choice for elective cases [6,9,10]. Repeated thoracenteses and chest tube insertion are also unsatisfactory because of the high risk of complications and recurrence of hydrothorax [8].…”
Section: Discussionmentioning
confidence: 99%